Removal performance of elemental mercury by low-cost adsorbents prepared through facile methods of carbonisation and activation of coconut husk. Issue 1 (January 2015) - Johari, Khairiraihanna; Alias, Afidatul Shazwani; Saman, Norasikin; Song, Shiow Tien; Mat, Hanapi
The preparation of chars and activated carbon as low-cost elemental mercury adsorbents was carried out through the carbonisation of coconut husk (pith and fibre) and the activation of chars with potassium hydroxide (KOH), respectively. The synthesised adsorbents were characterised by using scanning electron microscopy, Fourier transform infrared spectroscopy and nitrogen adsorption/desorption analysis. The elemental mercury removal performance was measured using a conventional flow type packed-bed adsorber. The physical and chemical properties of the adsorbents changed as a result of the carbonisation and activation process, hence affecting on the extent of elemental mercury adsorption. The highest elemental mercury (Hg°) adsorption capacity was obtained for the CP-CHAR (3142.57 µg g −1 ), which significantly outperformed the pristine and activated carbon adsorbents, as well as higher than some adsorbents reported in the literature.